Методология развития научных основ формирования экономически эффективных и экологически безопасных операций сквозных технологий лесозаготовок - Vasilyev A. S. (Scientific studies: theory, methodology and practice, 2017)
the methodology of the development of scientific foundations for the formation of economically effective and environmentally safe operations of end-to-end technologies of forestry industries through their improvement based on the construction of "intellectual matrices" is considered.
Keywords: методология; лесозаготовки; сквозные технологии; methodology; интеллектуальные матрицы; logging; освоение древесных ресурсов; intellectual matrices; end-to-end technologies; development of wood resources